2015
DOI: 10.1021/tx5005369
|View full text |Cite
|
Sign up to set email alerts
|

Steroidomic Footprinting Based on Ultra-High Performance Liquid Chromatography Coupled with Qualitative and Quantitative High-Resolution Mass Spectrometry for the Evaluation of Endocrine Disrupting Chemicals in H295R Cells

Abstract: The screening of endocrine disrupting chemicals (EDCs) that may alter steroidogenesis represents a highly important field mainly due to the numerous pathologies, such as cancer, diabetes, obesity, osteoporosis, and infertility that have been related to impaired steroid-mediated regulation. The adrenal H295R cell model has been validated to study steroidogenesis by the Organization for Economic Co-operation and Development (OECD) guideline. However, this guideline focuses solely on testosterone and estradiol mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The decrease in progesterone levels in the offspring could suggest a decrease in steroidogenic enzyme expression, as some in vitro steroidogenesis studies showed down‐regulation of progesterone and 17α‐hydroxyprogesterone levels after TCC exposure, impairing an early step of steroidogenesis (Strajhar et al, ; Tonoli et al, ). Moreover, the steroidogenic acute regulatory protein (StAR) plays a critical role in steroidogenesis, transporting cholesterol from the outer to the inner mitochondrial membrane and a decreased StAR expression has been reported in fathead minnows (Zenobio, Sanchez, Archuleta, & Sepulveda, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in progesterone levels in the offspring could suggest a decrease in steroidogenic enzyme expression, as some in vitro steroidogenesis studies showed down‐regulation of progesterone and 17α‐hydroxyprogesterone levels after TCC exposure, impairing an early step of steroidogenesis (Strajhar et al, ; Tonoli et al, ). Moreover, the steroidogenic acute regulatory protein (StAR) plays a critical role in steroidogenesis, transporting cholesterol from the outer to the inner mitochondrial membrane and a decreased StAR expression has been reported in fathead minnows (Zenobio, Sanchez, Archuleta, & Sepulveda, ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in progesterone levels in the offspring could suggest a decrease in steroidogenic enzyme expression, as some in vitro steroidogenesis studies showed down-regulation of progesterone and 17α-hydroxyprogesterone levels after TCC exposure, impairing an early step of steroidogenesis (Strajhar et al, 2017;Tonoli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-variables which combine high magnitude and high reliability are of relevance in the search for discriminating variables. The extraction of the discriminating variables from the S-plot could be combined with the jack-knifed confidence intervals seen in the loading plot [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in contrast to the hypothesis that TCC can augment androgenic activity, these data were more suggestive of a potential antiandrogenic action than augmentation. At least 1 recent study suggests that TCC may impair steroid biosynthesis in vitro . However, the concentrations tested in H295R cells were in excess of 150 µg/L , so it is unclear whether those effects would be relevant in vivo given that similar concentrations cause overt toxicity in fish.…”
Section: Discussionmentioning
confidence: 99%